Legislative Leviathan Party Government in the House (Second Edition) - Cox, Gary W (Cambridge University Press, 2013)
Scholars who compare political parties invariably conclude that American parties are much weaker than their European counterparts: they are much less cohesive on legislative votes; their influence over the flow of legislation is less complete; they control but a small fraction of campaign money; they exercise almost no control over nominations; the list could go on. Within the American context, observers have commonly concluded that parties influence legislators less than pressure groups, political action committees, or constituents